Design and development of multi-band antennas for ITS applications - Fan, Yunfei (2016)
Cars play an important role in lots of people’s everyday life. However, traffic congestion and traffic incidents bring a lot of trouble to them. Although, driverless cars can help people to improve the current situation, it estimates that a publicly available autonomous car still needs at least 10 years. The purpose of this report is to find out a design and fabrication method for the low cost multi-band antenna, which is based on the V2X concept for Intelligent Transportation Systems (ITS). The antenna will help to improve the traffic efficiency and safety. This report will include two approaching methods: planar antenna design and monocone antenna design, with their corresponding simulated and modified results. Furthermore, this report contains the ideas of fabrication, and the final product of the monocone antenna. The results of simulation and measurement showed that monocone antenna design was more suitable than planar antenna design for the ITS system, and self-made method for monocone antenna fabrication was applicable. However, the final testing results were not so perfect due to lack of experience in self-fabrication. Further studies can be done by adjusting the components of the antenna during fabrication, such as materials and cutting methods of shorting pins, top plane and top ring, in order to enhance the precision of the experiment. Moreover, this low cost manufacturing method can be considered to apply to fabricate other types of antennas.